Thinning enhances success of enrichment planting with selected tree species under a pure stand of Leucaena leucocephala - Oliveira, Carlos D. C. [UNESP]; Melo, Antônio C. G.; Durigan, Giselda [UNESP] (Wiley, 2023)
Increasing the biodiversity of Leucaena leucocephala (hereafter leucaena) stands without losing the benefits provided by the forest structure is a challenge for adaptive management. Here, we report the survival and growth (height, stem, and canopy diameter) of five Atlantic Forest tree species planted underneath a pure stand of the exotic leucaena, which was broadcast sown 35 years before in a 0.6 ha area. Two treatments were compared: thinning (cutting all leucaena trees in 4‐m wide rows, where seedlings were planted) and control (seedlings planted under leucaena canopy), with four replicates each (20 seedlings per plot, four per species, 2‐m spaced). The five species selected were long‐lived emergent trees from seasonal forests, with broad canopy, evergreen, and shade‐tolerant. These traits were expected to allow their survival and growth, and, later on, to shade out the leucaena trees. Seven years after planting, survival was high for all species (around 80%), not differing between treatments or species. On average, stem diameter, height, and crown diameter were, respectively, 69, 44, and 36% higher in thinned than in control plots. Response to thinning differed between species in growth, with Gallesia integrifolia and Luehea divaricata standing out. Our results demonstrate that the species used for enrichment planting, selected by their suitable functional traits, can successfully survive under leucaena stands. Reducing competition by thinning, however, is crucial to enhance their growth. Despite the benefits from thinning, enrichment success strongly depends, therefore, on the abilities of the species selected to face the ecological filters acting on the target ecosystem.